2020
DOI: 10.30684/etj.v38i3a.483
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Settlement of Footings of Different Shapes Resting on Clayey Soil

Abstract: An experimental investigation is carried out to investigate the impact of the footing shape, when rested on clayey soil under cyclic loading condition. The model footings used in this study are circular, square and the area of footings is fixed. Cyclic load test is carried out on the cohesive soil with three undrained shear strengths (20 kPa, 40 kPa and 70 kPa). Two depths of foundation embedment (at surface and 5 cm) to know the effect of the depths of the foundations on the change of settlement and total ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Results of their study showed an overall decrease of 65% in peak tensile strains in the reinforced part when compared with unreinforced section. An experimental investigation was conducted by [8]to investigate the shape of footing's impact, when rested upon clayey soil under cyclic loading condition. It was observed that the bearing capacity varies in increasing order as solid circular and square.…”
Section: Introductionmentioning
confidence: 99%
“…Results of their study showed an overall decrease of 65% in peak tensile strains in the reinforced part when compared with unreinforced section. An experimental investigation was conducted by [8]to investigate the shape of footing's impact, when rested upon clayey soil under cyclic loading condition. It was observed that the bearing capacity varies in increasing order as solid circular and square.…”
Section: Introductionmentioning
confidence: 99%
“…Najim et al [14]investigated the effect of the shape of footing when resting on clay soil under cyclic loading conditions. Cyclic load testing was carried out on the cohesive soil with three untrained shear strengths (20 kPa, 40 kPa and 70 kPa).…”
Section: Introductionmentioning
confidence: 99%
“…Two configurations of the instrumented model piles were assembled: The Force sensitive resistor (FSR) sensors were placed at the pile head, the instrument adopted provided measurement of the axial loads transferred to each instrumented pile. While the other FFS sensor is used for contact pressure measurements placed under the raft [18] & [19], the tactile load sensors were not located in the soil; they were fixed to the pile cap surface by adhesive tape.…”
Section: Procedures Of Testsmentioning
confidence: 99%